Ethnobotanical and Biochemical Study of Berberis lycium Royle Collected from Different Areas of Azad Jammu and Kashmir. (26th September 2021) - Fiaz Bukhari, Syeda Maria; Ali, Ghazanfar; Abbas, Syed Rizwan; Anjum, Zeeshan; Ahmed, Nasim; Munir, Ammara; Wali, Abdul; Ayub, Muhammad; Khan, Kafaitullah; Khames, Ahmed; Musthafa, Muneeb Muhamed
Abstract : Berberis lycium Royle has a long history of medicinal uses to treat different diseases. It naturally grows on the mountains of Indian subcontinent. Its ethnobotanical and biochemical study from the state of Azad Jammu and Kashmir (AJ&K) was not previously explored. So, the objective of the current study was to explore the ethnobotanical and biochemical properties of the B. lycium Royle population of AJ&K. For this purpose, samples of B. lycium Royle were randomly collected from five districts of Azad Jammu and Kashmir, including thirty-five locations . Demographic features of informants such as plant part used, methods of preparation, modes of administration, conservation status, and ethnomedicinal uses were documented. It was used for treating different diseases such as diabetes, arthritis, joint pain, and stomach ulcer. This plant is very famous for providing medicinal roots, leaves, and fruits which are extensively used in many parts of the world. The biochemical analysis was conducted for total phenolic contents (TPC), chlorophyll contents, and antioxidant activity. The highest level of TPC found was 88.66 ± 1.07  µ g/g of gallic acid equivalent phenolic (GAE) from leaves collected from Patikka (Chanjhal), Muzaffarabad District, AJ&K. The highest total chlorophyll contents (3.75 ± 0.53  µ g/ml) were found in samples collected from Sathrian, Neelum District. The highest antioxidant activity with lowest IC50 value (33.26  µ g/ml) was obtained from the root of sample collected from Bakreyali, Muzaffarabad District, as compared with other districts. The concentration of berberine was found to be 4.76 percent in the root bark of B. lycium Royle, estimated by high-performance liquid chromatography (HPLC). In syrup composition, 0.95 mg/5 ml of berberine was used. Hence, it is concluded that amongst the five districts, the plant parts (stem, fruits, and root) collected from Muzaffarabad District, AJ&K, showed the highest medicinal potential due to its unique climatic conditions.